2000
DOI: 10.1248/bpb.23.884
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylenes from Angelica gigas and Their Inhibitory Activity on Nitric Oxide Synthesis in Activated Macrophages.

Abstract: In activated macrophages the inducible form of nitric oxide synthase (i-NOS) generates high amounts of the toxic mediator, nitric oxide (NO) which contributes to the circulatory failure associated with septic shock. Two polyacetylenes were isolated from the medicinal plant Angelica gigas and their structures were elucidated as octadeca-1,9-dien-4,6-diyn-3,8,18-triol (1) and 18-acetoxy-octadeca-1,9-dien-4,6-diyn-3,8-diol (2) by spectroscopic method. These polyacetylenes and their peracetate, 3, 8, 18-triacetoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…When the sonication extraction method was used, the content of compounds was higher than in the reflux method. To determine the time needed for complete extraction, samples were extracted for five different lengths of time (15,45,60,90, and 120 min) using a 70% ethanol solvent and the sonication extraction method. When the extraction time was 45 min, the results were similar to those at 60 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sonication extraction method was used, the content of compounds was higher than in the reflux method. To determine the time needed for complete extraction, samples were extracted for five different lengths of time (15,45,60,90, and 120 min) using a 70% ethanol solvent and the sonication extraction method. When the extraction time was 45 min, the results were similar to those at 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] The plants of A. sinensis and A. acutiloba are quite similar in their constituents except for the content of compounds. In spite of the fact that A. gigas, A. sinensis, and A. acutiloba belong to the same genus, there are definite differences in the components and medicinal effects each species has.…”
mentioning
confidence: 99%
“…Several chemical groups acting as iNOS inhibitors such as lignans (Matsuda et al, 2001), sesquiterpenes (Dirsch et al, 2000;Kim et al, 2001), alkaloids (Liu et al, 1994), polyacetylenes (Matsuda et al, 1998;Choi et al, 2000) and flavonoids have been reported from diverse plants, and this is the first report of butanolides being an iNOS inhibitor. Several butanolides with a β-hydroxy-γ-methyl-α, β-unsaturated-γ-lactone moiety from plants were reported as having strong cytotoxicity against tumour cells (Chen et al, 1998;Kwon et al, 2000), and our compounds are also expected to be cytotoxic against tumour cells.…”
Section: Resultsmentioning
confidence: 91%
“…Many studies have examined the pharmacological properties of A. gigas Nakai such as its antibacterial, anticancer, antitumor, antioxidant, anti-inflammatory, neuroprotective, anti-dementia, inhibition of platelet aggregation, and blood coagulation activity (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Based on these pharmacological properties, efforts have been made to isolate the active constituents from this plant.…”
Section: Introductionmentioning
confidence: 99%